Adjuvant drugs in management of osteoarthritis: spotlight on type II collagen - Kakatkar, Vijay; Pal, A. K.; Reddy, Raghuveer; Dashputra, Ravi; Kamble, Sanjay; Saresa, Hiten; Jain, Rishi (International Journal of Research in Orthopaedics, 2019)
Osteoarthritis (OA) is a common musculoskeletal disorder that affects large and small joints and is seen in all ages due to diverse aetiologies. Pain, joint stiffness and limitation of daily activities affects the quality of life of individuals with OA. Conventional analgesics like non-steroidal anti-inflammatory drugs affect pain and inflammatory component but do not target the disease pathogenesis. Damage to the joint cartilage is central to the pathogenesis of OA. Better understanding of the pathogenesis has led to evolution of various adjuvant drugs in management of OA. Among them, undenatured type II collagen induces immune tolerance and thereby provide benefits by reducing the joint damage. Studies assessing efficacy and safety of undenatured type II collagen in OA have shown to reduce clinical symptoms like pain, joint stiffness and improvement in physical activities, and thus improving the quality of life. It is well tolerated and safe for use in OA. This article discusses the pathophysiology of OA with inflammation and beyond, and overviews the various drugs that are used as adjuvants in the management of OA with special focus on the use of type 2 collagen.